THE EFFECT OF AGRICULTURAL EXPLANATION ON RICE PRODUCTIVITY (Oryza sativa L.) (Case: Kerapuh Village, Dolok Masihul District, Serdang Bedagai Regency) - Mutiara Pane (Agripreneur : Jurnal Pertanian Agribisnis, 2021)
The purpose of this study was to determine the implementation of the agricultural extension program in Kerapuh Village, Dolok Masihul District, Serdang Bedagai Regency. This study aims to determine the effect of agricultural extension factors on lowland rice productivity in Kerapuh Village, Dolok Masihul District, Serdang Bedagai Regency. The analytical method used in this research is descriptive method and multiple linear regression analysis method using SPSS 17. Determination of the research location is done purposively. The sampling technique used is simple random sampling method with a total sample of 52 respondents. This research was conducted in 2018. The results show that the characteristics of the most respondents are in the age group 51-55 years where the percentage is 37%, the education of the most respondents is at the elementary education level where the percentage is 37%, length of farming The highest number is in the group 21-25 where the percentage is 35%. The implementation of the agricultural extension program in Kerapuh Village, Dolok Masihul District, Serdang Bedagai Regency is quite good. Educational factors, length of time in farming, extension programs and competency of extension workers have a significant effect on productivity in the research area.